Mechanisms of an innovative hybrid arc welding process in enhancing joint penetration and weld property control through resistive and induction heat. (December 2021) - Ye, Zheng; Huang, Jihua; Cheng, Zhi; Wang, Shifei; Yang, Jian; Chen, Shuhai; Zhao, Xingke
Abstract: Low costs (material, energy and time), high joint properties are the eternal pursuit of modern welding. In this paper, mechanisms of an innovative high frequency electric cooperated arc welding (HFAW) in enhancing welding productivity (joint penetration) and weld property control were comprehensively investigated. The process properties and weld mechanisms of this method were systematically compared with that of the traditional GMAW welding under typical process parameters. The results showed that 4.8 mm joint with an large aspect ratio of 4 was achieved by single pass HFAW at a high welding speed (15 mm/s) and a low welding heat input (reduced 1/3 than the traditional GMAW). The research on weld property control shows that the microstructure of weld zone and heat affected zone (HAZ) in the HFAW joint was much smaller than that in the GMAW joint under optimal parameters. The width of each zone in the HAZ, thermal cycle parameters such as elevated temperature holding time and cooling rate can be regulated independently by the high frequency electric heat input ratio. Such regulation is of great significance for high strength steel welding, which needs to control the welding thermal cycle process accurately. Combined with three-dimensional solid reconstruction of liquid filler metal, the mechanism of the HFAW in enhancing joint penetration was demonstrated. An interesting "self-tracking heating" of the high frequency current was found. The cutting-edge of the liquid metal was violently heated and more than half of the weld in thickness direction was achieved by a novel ultra-speed "interfacial tension driving penetrating" weld forming mechanism, which promises the HFAW high welding speed and large aspect ratio on the premise of satisfactory welding quality. Graphical abstract: Unlabelled Image Highlights: A novel high frequency electric cooperated arc welding was systematically studied. 4.8 mm sound joint was achieved at a high welding speed (15 mm/s) by single pass. "Self-tracking heating" of the high frequency current was revealed. A novel "interfacial tension driving penetrating" weld forming mechanism was found. Physical model was established by a three-dimensional solid reconstruction method.